Regulation of LEF-1/TCF transcription factors by Wnt and other signals. - Eastman, Q.; Grosschedl, R. (Current Opinion in Cell Biology, 1999)
LEF-1/TCF transcription factors mediate a nuclear response to Wnt signals by interacting with beta-catenin. Wnt signaling and other cellular events that increase the stability of beta-catenin result in transcriptional activation by LEF-1/TCF proteins in association with beta-catenin. In the absence of Wnt signaling, LEF-1/TCF proteins repress transcription in association with Groucho and CBP. The LEF-1/TCF transcription factors can also interact with other cofactors and play an architectural role in the assembly of multiprotein enhancer complexes, which may allow for the integration of multiple signaling pathways.